Expanding Access to Improved Sanitation for the Poor : Insights from the Philippines - International Finance Corporation (International Finance Corporation, Washington, DC, 2018)
The Philippines is home to around twenty five million of the 2.3 billion people worldwide who lack access to a basic sanitation service. Poor sanitation has enormous economic and human costs. The spread of water-borne diseases, for instance, results in billions of dollars in costs to the government and poor quality of life for many citizens. IFC’s Inclusive Business team partnered with the Manila Water Foundation, which is Manila Water Company’s social responsibility arm established in 2005, to undertake a three-part study that would assess the reasons why low income urban households in the Philippines still do not have improved sanitation facilities and to test possible sanitation solutions that enable these households to improve their sanitation conditions. The study is part of IFC’s ongoing efforts to partner with the private and public sectors to promote inclusive and sustainable growth through market based solutions for the poor and underserved.The objectives of this study are to provide context for the sanitation conditions of low-income communities in the Philippines and to identify the opportunities and barriers to improving sanitation systems.